2017
DOI: 10.1111/ajad.12509
|View full text |Cite
|
Sign up to set email alerts
|

Differential prevalence of established risk factors for poor cessation outcomes among smokers by level of social anxiety

Abstract: Background and Objectives Despite clear associations between social anxiety (SA), high prevalence of smoking, and cessation failure, little is known about factors contributing to these relationships. Moreover, the extent to which smokers with moderate SA represent an at-risk group of smokers is also unknown. This study examined the extent to which established risk factors for poor cessation (e.g., sociodemographic, smoking history, mental health comorbidity) are prevalent among smokers with low, moderate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
1
2
1
Order By: Relevance
“…Individuals who screened positive for affective disorders may not all have the disorders they screened positive for and instead have elevated, subthreshold symptoms of the disorders. In line with previous research indicating that even individuals with subthreshold symptoms of affective disorders are at risk for continued smoking [3,46] and that screening instruments for affective disorders can be used to predict cessation [2], this study highlights that the screening instruments used in this study can be useful in identifying smokers who are less likely to quit even without a formal diagnostic assessment. Finally, we did not biochemically verify self-reported smoking abstinence at the 12-month follow-up.…”
Section: Discussionsupporting
confidence: 87%
“…Individuals who screened positive for affective disorders may not all have the disorders they screened positive for and instead have elevated, subthreshold symptoms of the disorders. In line with previous research indicating that even individuals with subthreshold symptoms of affective disorders are at risk for continued smoking [3,46] and that screening instruments for affective disorders can be used to predict cessation [2], this study highlights that the screening instruments used in this study can be useful in identifying smokers who are less likely to quit even without a formal diagnostic assessment. Finally, we did not biochemically verify self-reported smoking abstinence at the 12-month follow-up.…”
Section: Discussionsupporting
confidence: 87%
“…However, we observed that the patients who had the worst results (lowest score) were the same ones who did not cease and/or relapsed, while the patients who completely stopped had the best results in the evaluation of the lifestyle. In a recent study, Xue et al (2017), demonstrated that smokers who quit smoking after drug-eluting stents implantation showed comparable improvement health status and quality-of-life benefits when compared with nonsmokers and significantly better HRQoL than smokers who continued smoking [41]. However, in the aforementioned study, there was a compulsory need for post-infarction cessation, as opposed to the present study in which treatment was initiated voluntarily.…”
Section: Discussioncontrasting
confidence: 75%
“…In a study by Mitra et al (2004), it was demonstrated that individuals who quit smoking showed a significant improvement in mean SF-36 scores overtime for health in general, including the domains of mental health, energy, and vitality [40]. Accordingly, Xue et al (2017), who used SF36 as an instrument to evaluate patients with non-smokers coronary heart disease had a better health-related quality of life (HRQoL) than the smokers' group [41]. In our study, the evaluation after the smoking cessation treatment showed that the indicators of the LPA, SA, and EA domains had higher scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation